Investigation the antioxidant activity of benzo[g]triazoloquinazolines correlated with a DFT study - Abdulrahman A. Almehizia; Hatem A. Abuelizz; Hanan A.A. Taie; Anouar ElHassane; Mohamed Marzouk; Rashad Al-Salahi (Elsevier, 2019)
Previously, a series of 2-phenoxy-benzo[g]triazoloquinazolines 1-16 were synthesized and fully characterized. The antioxidant activity of the target molecules 1-16 was evaluated using three different assays namely 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging, ferric reduction antioxidant power (FRAP) and reducing power capability (RPC). The results revealed that some benzotriazoloquinazolines showed good activity and have the capacity to scavenge free radicals. In particular, compounds 1 and 14 have shown the highest activity. The butylated hydroxyl toluene (BHT) used as standard agent.Density functional theory was carried out to explain the relative importance of CO, CS and NH groups on the radical scavenging activity of the target benzotriazoloquinazolines. The finding in present study shows that the active compounds can be used as template for further development of more potent antioxidant agents. Keywords: Benzotriazoloquinazolines, DPPH, BHT, DFT, Antioxidant capacity